Opportunities for exploiting variations in haulm fodder traits of intermittent drought tolerant lines in a reference collection of groundnut (Arachis hypogaea L.) - Blümmel, Michael; Ratnakumar, P.; Vadez, Vincent (Elsevier, 2012)
Groundnut haulm has a great value as feed stock in the semi-arid tropics. Two-hundred-two and 194 cultivars of groundnut grown under intermittent water stress and fully irrigated treatment for two consecutive years at ICRISAT (2008/2009 and 2009/2010) in Patancheru in India were investigated for haulm fodder quality traits and for potential trade-offs between pod or haulm yield and haulm fodder traits. Highly significant (P < 0.0001) cultivars-dependent variations were found for a range of laboratory haulm fodder quality traits. Haulm nitrogen contents ranged from 1.94 to 2.88% and from 1.81 to 2.66% while in vitro digestibility ranged from 57.3 to 64.3% and from 59.5 to 64.2% under water restriction and fully irrigated conditions, respectively. Under fully irrigated conditions haulm nitrogen content and in vitro digestibility were mildly, but significantly inversely, related to pod yields with the two haulms traits accounting for 5 and 4% of the variations in pod yields. However, potential trade-offs between haulm traits and pod yields became more pronounced under water stress where variations in haulm nitrogen content and in vitro digestibility accounted for 40 and 28% of the variations in pod yields, respectively. For haulm nitrogen content and in vitro digestibility no significant interactions were observed between cultivar and treatment suggesting stability of haulm fodder traits across poorer and better water management practices. These results demonstrate that breeding for fodder traits in groundnut can be parallel to breeding for productivity traits, although careful choice of cultivars with high fodder trait value would be needed under water stress conditions.